Glycosylated gold nanoparticles in point of care diagnostics: from aggregation to lateral flow. (27th July 2022) - Baker, Alexander N.; Hawker-Bond, George W.; Georgiou, Panagiotis G.; Dedola, Simone; Field, Robert A.; Gibson, Matthew I.
Abstract : Antibody-based lateral flow (immune) assays are well established, but here the emerging concept and potential of using glycans as the detection agents is reviewed. Abstract : Current point-of-care lateral flow immunoassays, such as the home pregnancy test, rely on proteins as detection units ( e.g. antibodies) to sense for analytes. Glycans play a fundamental role in biological signalling and recognition events such as pathogen adhesion and hence they are promising future alternatives to antibody-based biosensing and diagnostics. Here we introduce the potential of glycans coupled to gold nanoparticles as recognition agents for lateral flow diagnostics. We first introduce the concept of lateral flow, including a case study of lateral flow use in the field compared to other diagnostic tools. We then introduce glycosylated materials, the affinity gains achieved by the cluster glycoside effect and the current use of these in aggregation based assays. Finally, the potential role of glycans in lateral flow are explained, and examples of their successful use given.